2010
DOI: 10.1039/b919094e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of ionic liquids based on 1-butyl-3-methylimidazolium chloride and MCl4, M = Hf and Zr

Abstract: Dialkylimidazolium chlorometallate molten salts resulting from the combination of zirconium or hafnium tetrachloride and 1-butyl-3-methylimidazolium chloride, [C(1)C(4)Im][Cl], have been prepared with a molar fraction of MCl(4), R = n(MCl4)/n(MCl4) + n([C1C4IM][Cl]) equal to 0, 0.1, 0.2, 0.33, 0.5, 0.67. The structure and composition were studied by Differential Scanning Calorimetry (DSC), (35)Cl (263 to 333 K), (1)H and (13)C solid state and solution NMR spectroscopy, and electrospray ionisation (ESI) mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 45 publications
0
19
0
1
Order By: Relevance
“…96 It seems to be a reoccurring theme that MS results can lead to confusion and erroneous conclusions about speciation. Campbell et al 97 studied chlorohafnate(IV) and chlorozirconate(II) ionic liquids using a multi-technique approach, which unfortunately did not include vibrational spectroscopy. Based on DSC and known coordination chemistry of both metals, they hypothesised the predominance of [MCl 6 ] 2À , [M 2 Cl 10 ] 2À and (unknown in the literature) [M 2 Cl 9 ] À at w MCl 4 = 0.33, 0.50 and 0.67, respectively.…”
Section: Electron Paramagnetic Resonance (Epr)mentioning
confidence: 99%
“…96 It seems to be a reoccurring theme that MS results can lead to confusion and erroneous conclusions about speciation. Campbell et al 97 studied chlorohafnate(IV) and chlorozirconate(II) ionic liquids using a multi-technique approach, which unfortunately did not include vibrational spectroscopy. Based on DSC and known coordination chemistry of both metals, they hypothesised the predominance of [MCl 6 ] 2À , [M 2 Cl 10 ] 2À and (unknown in the literature) [M 2 Cl 9 ] À at w MCl 4 = 0.33, 0.50 and 0.67, respectively.…”
Section: Electron Paramagnetic Resonance (Epr)mentioning
confidence: 99%
“…The same behaviour was reported for ionic liquids containing excess aluminium chloride 12,16. Ionic liquids solely based on NbCl 5 ,17 TaCl 5 ,18 TiCl 4 ,19 ZrCl 4 ,20 or HfCl 4 21 were already reported. However, their mixtures with neutral chloroaluminate melts have not been described yet.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal stability of both ionic liquids, that is, [Bmim][FeCl 4 ] and [Bmim][SCN] under harsh thermal conditions was investigated by using the TGA analysis, and the results are illustrated in Figure . With the reference of [Bmim][FeCl 4 ] (Figure ), the TGA analysis revealed that initially, the significant weight loss of the ionic liquid [Bmim][FeCl 4 ] was identified at a temperature within the range of 43.8°C with loss in weight of approximately 7.8% . This initial loss in weight of the [Bmim][FeCl 4 ] sample can be directed to the evaporation of the trapped water molecules present in the [Bmim][FeCl 4 ], which were absorbed from the atmosphere during the experimentation.…”
Section: Resultsmentioning
confidence: 99%